THE EFFECT OF SEVERAL CONCENTRATIONS OF GLYCINE AMINO ACID ADDITIONS IN MS MEDIUM TOWARS CALLUS GROWTH OF KONJAC (Amorphophallus muelleri) BY in vitro CULTURE - Rizka Anisa Rennytasari; Paramita Cahyaningrum Kuswandi (Kingdom (The Journal of Biological Studies), 2022)
Konjac (Amorphophallus muelleri) is a plant that can be a source of carbohydrates and has high economic value. To accelerate the fulfillment of porang seeds in order to support maximum economic potential, it is necessary to develop alternative propagation techniques,which is in vitro culture. This study aimed to determine the effect of adding the glycine amino acid to MS medium on the growth of konjac callus and to determine the best concentration for callus growth in konjac plant tissue culture. This research was using frog bulb (bulbil) for the explant. In this study used a completely randomized design (CRD) with glycine amino acid concentrations from 0 mg/L, 1 mg/L, 2 mg/L, 3 mg/L, 4 mg/L, dan 5 mg/L with 3 replications. Data were analyzed using SPSS software with one way ANAVA and further test using DMRT 5%.The results showed that the addition of the glycine amino acid to MS medium affected the callus growth of konjac plant tissue culture based on the analysis of variance (ANAVA) test. The best concentration used based on the Duncan Multiple Range Test (DMRT) 5%, was 4 mg/L with the average callus appearance time of 3.06 wac and the average bending time of 2.1 wac.